Kualitas Pelayanan Administrasi Terpadu Kecamatan (PATEN) di Kantor Camat Cambai Kota Prabumulih - Trianza, Deni; Sunarto, Sunarto; Wulandari, Novita (Journal of Law & Policy Review, 2024)
This article or writing aims to describe and analyze the Quality of District Integrated Administrative Services (PATEN) at the Cambai City Prabumulih Office, as well as identifying supporting and inhibiting factors for the Quality of District Integrated Administrative Services (PATEN) at the Cambai City Prabumulih Office. Data was collected through observation, interviews and documentation and analyzed qualitatively.  This study shows that public perceptions of the quality of population administration services in Sukaraja Village, Cambai District, Prabumulih City vary. Most respondents rated the service as “good” (47.70%), “very good” (33.8%), or “fairly good” (18%), while 0.50% rated it as “not good”. Factors that influence service quality include tangible dimensions (facilities and infrastructure), reliability (accuracy and trust), empathy (understanding), and responsiveness (speed and thoroughness). These findings provide insight into the public's assessment of services and the influencing factors.